Mixed acinar-neuroendocrine-ductal carcinoma of the pancreas: a tale of three lineages. (2nd June 2016) - Anderson, Mark J; Kwong, Christina A; Atieh, Mohammed; Pappas, Sam G
Abstract : Most pancreatic cancers arise from a single cell type, although mixed pancreatic carcinomas represent a rare exception. The rarity of these aggressive malignancies and the limitations of fine-needle aspiration (FNA) pose significant barriers to diagnosis and appropriate management. We report a case of a 54-year-old man presenting with abdominal pain, jaundice and a hypodense lesion within the uncinate process on CT. FNA suggested poorly differentiated adenocarcinoma, which was subsequently resected via pancreaticoduodenectomy. Pathological analysis yielded diagnosis of invasive mixed acinar-neuroendocrine-ductal pancreatic carcinoma. Given the rare and deadly nature of these tumours, clinicians must be aware of their pathophysiology and do practice with a high degree of clinical suspicion, when appropriate. Surgical resection and thorough pathological analysis with immunohistochemical staining and electron microscopy remain the standards of care for mixed pancreatic tumours without gross evidence of metastasis. Diligent characterisation of the presentation and histological findings associated with these neoplasms should continue in order to promote optimal diagnostic and therapeutic strategies.